P1-S1.28 The prevalence and incidence of bacterial vaginosis in a cohort of young Australian women. (10th July 2011) - Walker, J; Hocking, J; Fairley, C; Tabrizi, S; Chen, M; Bowden, F; Gunn, J; Donovan, B; Kaldor, J; Bradshaw, C
Abstract : Background: Bacterial vaginosis (BV) is a common condition of unknown aetiology that can be associated with late miscarriage, pre-term delivery, PID and increased susceptibility to HIV & other STIs. In Australia, treatment is restricted to women who are symptomatic or pregnant or undergoing gynaecological treatment, however, recurrent infection is common following treatment. Currently, there are no community based BV prevalence or incidence data for Australia. Methods: Women aged 16 to 25 years were recruited from sexual health clinics (SHC) and general practice clinics (GP) in South-Eastern Australia and provided with kits containing vaginal swabs and microscope slides to self-collect vaginal smears at 0, 6 and 12 months; 6- and 12-month samples were returned via post. Vaginal smears were scored using the Nugent method. BV prevalence was measured at time of recruitment and adjusted ORs (AOR) calculated to explore associations; BV incidence was measured over the study period and adjusted HRs (AHR) calculated to explore predictors of infection. Incident BV was diagnosed if a participant at baseline had a Nugent score <7 followed by a subsequent Nugent score of 7–10 at 6 or 12 months. Women diagnosed with BV at recruitment were excluded from the incidence analysis. Results: Overall, 1116 women were recruited from 29 clinics; slides were available for 1112 (99%) women at the baseline and 875 women (79%) at study completion. The prevalence of BV at recruitment was 11.8% (95% CI 9.9 to 13.7). Prevalent BV was associated with increased numbers of recent male sexual partners (AOR=2.2; 95% CI 1.0 to 4.6), a recent female sexual partner (AOR=3.2; 95% CI 1.6 to 6.5), being recruited from SHC (AOR=1.7; 95% CI 1.1 to 2.5) and having a lower level of education (AOR=0.5; 95% CI 0.3 to 0.7). There were 88 cases of incident BV yielding an incidence of 8.8 per 100 women years (95% CI 7.1 to 10.8). Incident BV was associated having increased numbers of new sexual partners (AHR=1.7; 95% CI 1.1 to 2.5). Both prevalent and incident infections were associated with increased numbers of self-reported symptoms, in particular "abnormal vaginal discharge" and "abnormal vaginal odour". Conclusion: These are Australia's first community-based BV prevalence and incidence estimates and show that BV is very common among young women and frequently associated with increased sexual activity.